Equal pay demand, 1945 (1945)
1945 1939-1945 "Equal pay demand, 1945" [T0233.jpg], 1945, Daily Express This press cutting from the 'Daily Express' of 22 September 1945 reports on various industrial disputes, including a threat of strike action from women engineering workers in North East over a demand for equal pay.